Using the Delone and McLean Success Model to Evaluate Moodle's Information System Success - Alduaij, Manal Y.; Alterkait, Mariam A.; Alainati, Shaikhah (Engineering, Technology & Applied Science Research, 2024)
This study evaluated the Moodle Professional Learning Management System (PLMS), based on user experience during the global pandemic of COVID-19, to explore the impact of system, service, information, education, learner, and instructor qualities on user satisfaction (SAT), perceived ease of use (PEOU), and perceived usefulness (PU). Data were collected using previously validated scales. Using SmartPLS structural equation modeling, data from 403 college students were analyzed to test 22 hypotheses. The results show that system and information quality positively affect PEOU. Although service quality had a partially significant impact on PU, it negatively affected SAT and PEOU. The quality of the education system had a partially positive impact on PU but a negative impact on PEOU and SAT. Learner quality positively affected PEOU, PU, and SAT. Although PU and PEOU significantly and positively affected benefits (BEN), SAT had only a partially significant impact. The results support the need for continued integration of e-learning with traditional learning schemas. This comprehensive analysis demonstrates how quality dimensions affect user experiences and outcomes in a unique cultural and emergency context, thus contributing to the e-learning body of knowledge.